The FTIR-ATR spectroscopy and Multivariate Data Analysis (MVDA) for halal authentication of animal fatty acids - Nazri, Muhammad Zulhelmi; Abd Rashid, Siti Nor Azlina; Ab Malik, Salimah; A. Karim, Hajar Aminah; Abdullah Sani, Muhamad Shirwan; Abang Zaidel, Dayang Norulfairuz (Malaysian Institute of Chemistry, 2024)
The authentication of halal products is crucial for adherents of Islam, as consuming nonpermissible substances contradicts religious mandates. The recent widespread adulteration of food and pharmaceutical products with porcine-derived ingredients has necessitated the development of robust analytical methods for halal verification. This study presents an approach for rapid halal authentication using Fourier transform infrared spectroscopy with attenuated total reflectance (FTIR-ATR), combined with multivariate data analysis (MVDA). Animal fats, i.e., beef, chicken, pork (lard), and goat, and a plant-based oil, i.e., palm oil, were extracted via Soxhlet apparatus utilising petroleum ether as solvent. The FTIR-ATR spectra were acquired in the mid-infrared region (4000 – 650 cm-1 ), encompassing both fingerprint and functional group regions. Principal component analysis (PCA) was employed to identify unique spectral patterns and develop classification models for halal authentication. The combination of FTIR-ATR and MVDA techniques enables the identification of characteristic spectral features and developing classification models for halal authentication. The PCA results revealed distinct clustering of samples based on their origin, with total variance range of 74.75 – 98.79%, explained by the first two principal components based on all wavenumbers in the 4000 – 650 cm-1 FTIR spectra. This FTIR-ATR coupled with the MVDA approach offers a rapid, non-destructive, and cost-effective method for halal authentication. The approach’s high sensitivity and specificity make it a promising tool for regulatory bodies and food manufacturers to ensure compliance with halal standards.